Telehealth in surgery: an umbrella review. Issue 11 (12th October 2021) - Smith, Sarah M.; Jacobsen, Jonathan Henry W.; Atlas, Alvin P.; Khoja, Adeel; Kovoor, Joshua G.; Tivey, David R.; Babidge, Wendy J.; Clancy, Bridget; Jacobson, Erica; O'Neill, Christine; North, John B.; Wu, Roxanne; et al.
Abstract: Background: Telehealth use has increased worldwide during the COVID‐19 pandemic. However, hands‐on requirements of surgical care may have resulted in slower implementation. This umbrella review (review of systematic reviews) evaluated the perceptions, safety and implementation of telehealth services in surgery, and telehealth usage in Australia between 2020 and 2021. Methods: PubMed was searched from 2015 to 2021 for systematic reviews evaluating real‐time telehealth modalities in surgery. Outcomes of interest were patient and provider satisfaction, safety, and barriers and facilitators associated with its use. Study quality was appraised using the AMSTAR 2 tool. A working group of surgeons provided insights into the clinical relevance to telehealth in surgical practice of the evidence collated. Results: From 2025 identified studies, 17 were included, which were of low to moderate risk of bias. Patient and provider satisfaction with telehealth was high. Time savings, decreased healthcare resource use and lower costs were reported as key advantages of the service. Inability to perform comprehensive examinations was noted as the primary barrier. In Australia, peak telehealth usage coincided with the introduction of temporary telehealth services and increased lockdown measures. Conclusions: Patients and providers are broadly satisfied with telehealth and its benefits. Barriers may be overcome via multidisciplinary collaboration. Telehealth may benefit surgical care long‐term if implemented correctly both during and after the COVID‐19 pandemic. Abstract : An umbrella review was conducted evaluating the perceptions, safety and implementation of telehealth services in surgery, and telehealth usage in Australia between 2020 and 2021. Patient and provider satisfaction with telehealth was high, with time savings, decreased healthcare resource use and lower costs reported as key advantages. In Australia, peak telehealth usage coincided with the introduction of temporary telehealth services and increased lockdown measures.